2013
DOI: 10.1017/s0022149x13000333
|View full text |Cite
|
Sign up to set email alerts
|

Tandem antioxidant enzymes confer synergistic protective responses in experimental filariasis

Abstract: Helminth parasites use antioxidant defence strategies for survival during oxidative stress due to free radicals in the host. Accordingly, tissue-dwelling filarial parasites counteract host responses by releasing a number of antioxidants. Targeting these redox regulation proteins together, would facilitate effective parasite clearance. Here, we report the combined effect of protective immune responses trigged by recombinant Wuchereria bancrofti thioredoxin (WbTRX) and thioredoxin peroxidase (WbTPX) in an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Similarly, mice had some protection against Brugia malayi when immunized a DNA vaccine cocktail which included thioredoxin peroxidase (Anand et al 2008; Vanam et al 2009). Interestingly, there was a noted synergistic protective response when mice immunized both Wuchereria bancrofti thioredoxin and thioredoxin peroxidase in an experimental filarial model when challenged with B. malayi larvae (Prince et al 2013). A similar synergistic protective effect was noted in mice immunized against Helicobacter pylori superoxide dismutase, catalase, and thioredoxin peroxidase (Stent et al 2012).…”
Section: Implications For Future Tick Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mice had some protection against Brugia malayi when immunized a DNA vaccine cocktail which included thioredoxin peroxidase (Anand et al 2008; Vanam et al 2009). Interestingly, there was a noted synergistic protective response when mice immunized both Wuchereria bancrofti thioredoxin and thioredoxin peroxidase in an experimental filarial model when challenged with B. malayi larvae (Prince et al 2013). A similar synergistic protective effect was noted in mice immunized against Helicobacter pylori superoxide dismutase, catalase, and thioredoxin peroxidase (Stent et al 2012).…”
Section: Implications For Future Tick Researchmentioning
confidence: 99%
“…Interestingly, antioxidant enzymes are currently being evaluated for their usefulness in developing antiparasitic drugs and as antiparasitic vaccines (Pal & Bandyopadhyay, 2012;Prince et al, 2013). A variety of inhibitors designed to target glutathione reductase or thioredoxin reductase from Plasmodium falciparum have shown marked antimalarial activity (Pal & Bandyopadhyay, 2012), which underscores the central role of the parasitic antioxidant system to the parasite's survival.…”
Section: Implications For Future Tick Researchmentioning
confidence: 99%
“…In fact, one of our studies showed that a trivalent fusion protein rBm HAX (HSP12.6 + ALT-2 + TPX-2) vaccine conferred 67.5% protection in the mouse model ( 30 ). Immunization with TPX-2 skewed the protective immune response to a Th1 bias ( 30 , 41 , 43 ). Therefore, we hypothesized that a tetravalent fusion protein could generate a more balanced Th1/Th2 response and will be more effective as a prophylactic vaccine against LF infection.…”
Section: Introductionmentioning
confidence: 99%
“…Animals were handled in accordance with the institutional guidelines, and the experimental procedures were approved by an Institutional animal care committee. A group of animals each containing five jirds were immunized intraperitoneally with 50 μ g of FEP along with an equal volume of alum (Sigma‐Aldrich) . Control groups were immunized with alum alone.…”
Section: Methodsmentioning
confidence: 99%
“…The 96‐well microtitre plates (Nunc, Maxisorp; Nalge Nunc International, Denmark) were used, and the wells were coated with FEP (optimum conc. 100 ng/well) prepared in 100 μ l of coating buffer and incubated overnight at 4 °C . After washing and blocking with 5% skim milk solution, a serial twofold dilution of FEP antisera was carried out.…”
Section: Methodsmentioning
confidence: 99%